Pengaruh Posisi Knee-Chest Terhadap Kenyamanan Ibu Hamil Dengan Presentasi Sungsang - Nurul Azizah; Rafhani Rosyidah; Ratna Dwi Jayanti (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MOJOKERTO), 2026)
Breech presentation pregnancies often cause physical discomfort and anxiety, which can impact maternal well-being. The knee-chest intervention is a non-pharmacological intervention that, physiologically, has the potential to improve maternal comfort, but scientific evidence remains very limited. This study aimed to analyze the effect of the knee-chest position on the comfort of pregnant women with breech presentation, providing evidence that can inform clinical practice and improve patient care. This study used a quasi-experimental design with a control group, involving nineteen third-trimester pregnant women with breech presentation divided into an intervention group (n=10) and a control group (n=9). The intervention group received routine knee-chest exercises, while the control group received standard antenatal care. Comfort levels were measured using the General Comfort Questionnaire (GCQ) before and after the intervention. Data analysis was both descriptive and inferential, comparing changes in comfort scores across groups to ensure reliable results for healthcare professionals and researchers. The intervention group showed a significant increase in the total GCQ comfort score after the knee-chest intervention, encompassing physical, psychospiritual, and environmental aspects, compared with the control group. Clarifying how these improvements translate to maternal well-being can help readers assess practical benefits